Short Sales Are Almost Instantaneously Bad News: Evidence from the Australian Stock Exchange - Aitken, Michael J.; Frino, Alex; McCorry, Michael S.; Swan, Peter L. (Journal of Finance, 1998)
This paper investigates the market reaction to short sales on an intraday basis in a market setting where short sales are transparent immediately following execution. We find a mean reassessment of stock value following short sales of up to −0.20 percent with adverse information impounded within fifteen minutes or twenty trades. Short sales executed near the end of the financial year and those related to arbitrage and hedging activities are associated with a smaller price reaction; trades near information events precipitate larger price reactions. The evidence is generally weaker for short sales executed using limit orders relative to market orders.